Effect of IFRS 16 on the quality of financial reporting For the Iraqi economic units Applied to the General Company of Iraqi Airways - سلمان, عامر محمد; جاري, احمد سعد (Journal of Economics and Administrative Sciences, 2019)
The rental activity receives "significant" interest from accounting organizations interested in issuing accounting standards worldwide, such as the Financial Accounting Standards Board (FASB), the International Accounting Standards Board (IASB). As leases represents an important source of finance for economic units as an alternative to financing assets through purchase or borrowing. Professional organizations have focused on addressing the situation of extra-budgetary funding through which the lessee hides many leases that are classified as financing without It shows in the budget, which gives an incorrect picture of the reality of the financial situation of economic unity, IASB has issued IFRS 16, which terminates off- Balance sheet Financing by the lessee by recognizing all leases in the lessee's budget except for short-term contracts of one year, less, and less value of less than $ 5,000, Has been extended. The elimination of extra-budgetary funding is positively reflected "in the quality of financial reporting. The research examines the impact of IFRS 16 on the quality of the financial reporting of the Iraqi Airways Company as a charter entity and it deals with all leases as operating in line with the consolidated accounting system that is required to prepare its financial statements., and with Iraq's intention to adopt international standards, which started with the banking sector according to the instructions of the Central Bank by the end of 2016, the research provides a "modest" effort to adopt a model conforming to IFRS 16, Standardized accounting system in a vital sector of the Iraqi economy, a leasing sector. The research reached a number of conclusions, the most important of which are the following:                                          - IFRS 16 can be adopted in Iraq while maintaining the consolidated accounting system and utilizing the flexibility of the system to absorb the newly created accounts and the inclusion of accounting account numbers to suit them.                                       - A positive impact of IFRS 16 on improving the quality of the financial reporting of the Iraqi Airways Company is to reduce the voluntary entitlements of the company, thus enhancing the quality of financial reporting.                                                                   The most important recommendations reached by the research are:                                    - Iraqi economic units should apply the finance lease and offer the right to use the asset and lease liabilities within the statement of financial position separately from the rest of the items or under the same item that would have been presented if they had been held.- Updating the accounting guide in the consolidated accounting system to accommodate the changes resulting from the adoption of international standards, including the leases standard through the proposed model, and trying to formulate accounting models that adopt international standards after adjusting them to suit the Iraqi environment, similar to the proposed lease accounting model.